COMPARISON OF PAVEMENT STRUCTURES IN TUNNELS (Advances in Civil and Architectural Engineering, 2014)
Tunnels pose many fire risks. It is difficult to fight fires in tunnels due to their limited accessibility, the quantity of smoke, and high thermal radiation. Temperatures in tunnel fires can reach 1000 °C, and these fires can spread quickly and persist for long periods, the longest recorded in Europe lasting 53 h. The main requirements of tunnel pavement structures are driving safety and comfort, as well as low construction and maintenance costs. Choosing between using concrete or asphalt pavement structures in tunnels requires the assessment of many criteria, including safety, cost, ecology, and energy use. One must also consider the availability of technologies (finishers) and resources (bitumen or cement), as well as the probability of achieving the required contractor experience level, which impacts pavement management. This paper describes our analysis and process for deciding the pavement structure to be used in tunnels, as well as current European technical regulations for safe traffic flow in tunnels.